Pelatihan Bahasa Inggris untuk Anak-anak dengan Media Video Klip dan Latihan Terbimbing (Anotero Lembaga Scientific Pekanbaru, 2024)
English training activities for children with video clip media and guided training are the efforts of the devotion team to overcome the gap between limited English language hours in school and the benefits of learning English at childhood. The training was conducted at RT 01 RW 06 Tuah Madani Village in Pekanbaru City. Training participants are boys and girls aged 5-13 years. The training target is that the training participants have a mastery of basic vocabulary and expression on routines, body parts and clothing items. The training runs for 4 days with each meeting @ 3 x 40 minutes. The training method is (1) providing material through image media (2) Conducting intensive guidance so that each participant is able to have the language skills targeted by the instructor, (3) making interesting activities, such as a fast fighting competition by giving rewards (each participant gets a prize after previously successful answer questions/instructions from the instructor). The results showed that the participants could master the training targets through formative assessment and the training process took place with a pleasant and cheerful learning experience, although there were obstacles where a small part of students had difficulty following the material that was rather complex. Constraints are resolved by solving complex material into simpler and understood parts. Based on the activities that have been carried out, advice is given to parents and English teachers that children like English lessons even though their speed in learning is not the same.